2003
DOI: 10.1291/hypres.26.749
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Angiotensin II on Nitric Oxide Generation in Proliferating and Quiescent Rat Coronary Microvascular Endothelial Cells

Abstract: phospholipases C and D or protein kinase C (2). These transducers in turn regulate the expression of several growth factors, including platelet-derived growth factor and basic fibroblast growth factor (3). In contrast, AT2 is expressed in a few adult tissues, such as heart and kidney tissues, at low levels, and its activation has been implicated in growth inhibitory and/or proapoptotic effects as a result of stimulation of tyrosine phosphatase(s) (4). The results of recent studies suggest that co-stimulation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 38 publications
2
16
0
Order By: Relevance
“…Similar increases in these parameters have recently been reported in rat CMEC and aortic endothelial cells in which the effects of angiotensin II on NO production and eNOS mRNA/protein expressions were investigated in relation to the state of cell growth [20,31]. However, in the current study no marked difference was observed in iNOS activity between growing and quiescent rat CMEC in contrast to elevation in eNOS activity.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Similar increases in these parameters have recently been reported in rat CMEC and aortic endothelial cells in which the effects of angiotensin II on NO production and eNOS mRNA/protein expressions were investigated in relation to the state of cell growth [20,31]. However, in the current study no marked difference was observed in iNOS activity between growing and quiescent rat CMEC in contrast to elevation in eNOS activity.…”
Section: Discussionsupporting
confidence: 88%
“…However, the current data as to the effects of NO on endothelial cell growth are rather contradictory in that both growth-stimulating [3,10] and growth-inhibiting effects have been reported [27][28][29]. Besides, the effects of endothelial cell growth on the activity and expression of NAD(P)H oxidase remains to be fully elucidated, although the correlation between cell growth and enzymatic regulation of eNOS has recently been well-documented [20]. The present study was therefore designed to investigate the reciprocal relationship between coronary endothelial cell growth and the concurrent expression and activity of the enzymes, namely, eNOS and NAD(P)H oxidase that are associated with the regulation of endothelial cell redox state.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Losartan had no effect on basal ovarian blood flow in rats but blocked the ANG II-induced flow reduction, and, in contrast, the AT 2 receptor antagonist PD123319 increased ovarian basal blood flow and failed to reverse the effect of exogenous ANG II, indicating that under physiological conditions, ovarian blood flow of the rat is negatively regulated by ANG II through AT 2 receptors (Mitsube et al, 2003). Bayraktutan and Ulker (2003) suggested that ANG II stimulates NO production in rat coronary microvascular endothelial cells in both an AT 1 -and AT 2 -receptorregulated manner. Heinemann et al (1997) noted that intravenous injections of ANG II increased blood pressure, which was accompanied by a decrease in blood flow through the superior mesenteric artery and an increase in femoral blood flow, possibly due to vasodilatation; telmisartan prevented all of the hemodynamic responses, and the ANG II-evoked femoral vasodilatation was suppressed by L-NAME.…”
Section: Involvement Of Angiotensin II Receptors Other Than Angiotensmentioning
confidence: 94%
“…Indeed, the combinations of either atherogen with mevastatin, apocynin or losartan have led to reduced enzymatic activities compared to sole Ang II or PDGF-BB treatments. In this context, our previous studies have shown using endothelial cells that Ang II increases eNOS activity via concomitant involvement of its type 1 and type 2 receptor subtypes and also enhances cell proliferation and NADPH oxidase which are attenuated by MnTBAP, apocynin or antisense p22-phox (a pivotal subunit of NADPH oxidase) cDNA treatments [32][33][34]. [12].…”
Section: Discussionmentioning
confidence: 99%